PENGARUH PEMBERIAN DAUN JARAK, SINGKONG KEJU DAN SINGKONG KARET TERHADAP PERFORMANS DAN KONSUMSI ULAT SUTERASamia cynthia riciniINSTAR III-V - Deta Bili, Raynold Eben Ezer; Supartini, Nonok; Thiasari, Nurita (Fakultas Pertanian, 2018)
The purpose of this research was to find out the effect of Castor, Cheese cassava and Ceara rubber leaves to the performance (body weight, body length and cocoon weight) of silkworm Samia cynthia ricini instar III-V and its feeding consumption. This research was conducted from July to September 2016 at Aneka Ternak Laboratory of Tribhuwana Tunggadewi University. The material used in this research was silkworm Samia cynthia ricini. The method used in this study was a Completely Randomized Design (RAL) on 3 treatments with 4 replications. The treatment applied was P1 (Castor leaves feeding), P2 (cheese cassava leaves) and P3 (Ceara rubber leaves). The variables observed were the silkworm feeding consumption, and silkworm performance (body weight, body length and cocoon weight). The research data was analyzed using a Completely Randomized Design (RAL), if there is a real difference then continued with the Smallest Different Test (BNT). The results showed that the treatment of different types of leaves (Castor leaves, cheese cassava leaves and Ceara rubber leaves) on consumption of instar IV silkworm was not significant (P> 0.05), while the consumption of silkworm feed instar III and V was significantly different (P